Hip Arthroscopy vs Physical Therapy for Acetabular Labral Tears: Analysis of a Prospective Randomized Controlled Trial. Issue 7 (30th July 2018) - Stelzer, John W.; Agrawal, Ravi; Conaway, William; Quinlan, Noah J.; Upadhyaya, Shivam; Alpaugh, Kyle; Smith, Jennifer; Martin, Scott D.
Objectives: Hip arthroscopy is an effective surgical intervention for patients with symptomatic labral tears of the hip. However, there is debate as to which patients benefit from this procedure. Studies have shown that outcomes following arthroscopic labral repair in older patients have been unpredictable compared to the more predictable, positive outcomes commonly seen in younger populations. These older patients, who often have variable degrees of osteoarthritis, may benefit from non-surgical management, such as physical therapy, as a viable treatment modality. The purpose of this study was to compare the efficacy of physical therapy to hip arthroscopy for patients age 40 and older with a symptomatic labral tear. Methods: After IRB approval, patients were prospectively identified and randomized into one of two study arms: arthroscopic surgery (AS) or physical therapy (PT). A third study arm, dependent upon improvement with PT, was created as patients crossed over (CO) from PT to AS after a lack of improvement after a minimum of 8 weeks of PT. Criteria for eligibility included patients over the age of 40 with an MRI-confirmed symptomatic acetabular labral tear and limited radiographic arthritis, with exclusion of Tonnis grade 3 arthritis. AS consisted of labral repair or debridement if repair was not possible, and PT consisted of a uniform, comprehensive PT protocol guided by designated physical therapists. Demographic information, imaging studies, and baseline patient reported outcome measures (PROM) including the Modified Harris Hip Score (mHHS), Hip Outcome Score (HOS), Non-Arthritic Hip Score (NAHS), International Hip Outcome Tool (iHOT-33), and the Lower Extremity Function Score (LEFS) were collected at enrollment and at intervals of 6, 12, and 24 months after initiation of treatment. Statistical analysis was used to compare the AS, PT, and CO groups with respect to PROMs. Results: Of the 72 patients currently enrolled, 53 (73.6%) patients have completed at least 6-month follow-up, with an average follow-up of 15.2 months. Mean age was 47.0±4.8, and the mean Tonnis grade arthritis was 0.72±0.68 (range, 0-2). At the time of analysis, 13 (44.8%) of the 29 patients originally enrolled in the PT group crossed over (CO) to surgery. The AS and CO groups showed statistically significant improvements from enrollment to follow-up in all 6 PROMs; however, the PT group only showed statistically significant improvement from enrollment to follow-up in 1 PROM (Tables 1-3). When improvements of all three cohorts (AS, PT, CO) were compared, a statistically significant difference among the groups was observed in 4 of the 6 PROMs, and the surgical groups (AS and CO) outperformed the PT group (Table 4). Analysis of improvement between groups showed that CO significantly outperformed PT, while the data only approached statistical significance when AS outperformed PT. Conclusion: Although patients who undergo non-surgical management, such as PT, have shown potential to improve, results indicate that surgical intervention may be preferred over PT for patients over the age of 40 with symptomatic acetabular labral tears and limited radiographic arthritis. Additional patients and longer follow-up is necessary to confirm these findings. Table 1. Enrollment vs AT LEAST 6-month follow-up PROMs for Arthroscopic Surgery (As) group PROM Enrollment (n=24) Follow-Up (n=24) p-value mHHS 53.5 (49.0-57.5) 86.0 (71.5-87.0) .0006** HOS-ADL 0.705 (0.595-0.833) 0.956 (0.848-0.971) .0031** HOS-SSS 0.333 (0.236-0.573) 0.852 (0.489-0.967) .0005** NAHS 65.00 (51.88-73.75) 91.88 (80.63-93.75) .0006** LEFS 67.5 (59.0-78.5) 88.5 (78.0-96.0) .0014** IHOT-33 32.64 (29.00-49.72) 83.87 (59.51-91.19) .0015** All data is presented as Median (IQR) unless stated otherwise. *p<.05 **p<.01 Table 2. Enrollment vs AT LEAST 6-month follow-up PROMs for Physical Therapy (PT) group PROM Enrollment (n=16) Follow-Up (n=16) p-value mHHS 59.5(49.0-65.5) 68.5 (56.0-79.5) .1200 HOS-ADL 0.669 (0.600-0.809) 0.734 (0.632-0.890) .3255 HOS-SSS 0.337 (0.264-0.625) 0.500 (0.214-0.764) .4206 NAHS 58.75 (50.63-78.13) 70.00 (58.13-83.75) .0700 LEFS 66.5 (53.5-77.5) 67.0 (54.5-83.5) .8359 IHOT-33 34.51 (23.18-43.32) 49.78 (31.50-77.72) .0113* All data is presented as Median (IQR) unless stated otherwise. *p<.05 **p<.01 Table 3. Enrollment vs AT LEAST 6-month follow-up PROMs for Crossover (CO) group PROM Enrollment (n=13) Follow-Up (n=13) p-value mHHS 62.0 (51.0-69.0) 84.0 (76.0-87.0) .0064** HOS-ADL 0.719 (0.594-0.844) 0.912 (0.868-0.953) .0107* HOS-SSS 0.556 (0.139-0.650) 0.714 (0.600-0.893) .0024** NAHS 65.00 (55.00-76.25) 87.50 (83.75-93.75) .0057** LEFS 66.0 (50.0-79.0) 83.0 (76.0-94.0) .0052** IHOT-33 35.24 (25.22-51.09) 77.48 (74.03-80.42) .0019** All data is presented as Median (IQR) unless stated otherwise. *p<.05 **p<.01 Table 4. Comparison of the improvements from enrollment to follow-up of the AS, PT, and CO groups through Kruskal-Wallis Test PROM Arthroscopic Surgery (n=24) Physical Therapy (n=16) Crossover (n=13) p-value mHHS 21.0 (11.0-30.5) 7.0 (-5.0-15.5) 17.0 (13.0-35.0) .0241* HOS-ADL 0.143 (0.044-0.250) 0.022 (-0.037-0.617) 0.193 (0.103-0.406) .0408* HOS-SSS 0.352 (0.038-0.580) 0.014 (-0.097-0.250) 0.243 (0.194-0.444) .340* NAHS 18.13 (8.13-33.75) 6.25 (-0.63 -20.00) 11.50 (15.00-45.00) .0518 LEFS 13.0 (6.0-28.5) 1.5 (-7.0-6.5) 20.0 (10.0-43.0) .0157* IHOT-33 41.94 (4.03-60.50) 6.00 (2.89-24.24) 41.66 (32.29-56.31) .0627 All data is presented as Median (IQR) unless stated otherwise. * p<.05